2004
DOI: 10.1253/circj.68.1189
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Bone Marrow Implantation in Patients With Arteriosclerosis Obliterans, and the Association Between Efficacy and the Number of Implanted Bone Marrow Cells

Abstract: Background There have been a number of recent reports on the use of autologous bone marrow implantation (BMI) in the treatment of peripheral arterial disease, with a clinical response rate of approximately 70%. However, the factors that influence efficacy have not yet been clarified. We have analyzed the relationship between the number of implanted bone marrow cells and the clinical efficacy of BMI. Methods and ResultsEight patients with arteriosclerosis obliterans were treated with BMI. Bone marrow was aspira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 16 publications
6
78
0
4
Order By: Relevance
“…Therefore, it is possible that the number of CD34 þ cells has a dose-response relationship with OS and AFS. These result support the findings previously reported by Horie et al 18 and Saigawa et al 4 As all cells harvested were implanted in subjects in this study, we cannot distinguish between the effects of patient characteristics and the effects of implant quantity, but both factors could potentially influence a patient's prognosis. Kawamoto et al 20 found that the proportion of patients who had a CD34 þ cell yield of o10 6 cells/kg was as high as 35%, and that yields were especially low in older patients with ASO.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, it is possible that the number of CD34 þ cells has a dose-response relationship with OS and AFS. These result support the findings previously reported by Horie et al 18 and Saigawa et al 4 As all cells harvested were implanted in subjects in this study, we cannot distinguish between the effects of patient characteristics and the effects of implant quantity, but both factors could potentially influence a patient's prognosis. Kawamoto et al 20 found that the proportion of patients who had a CD34 þ cell yield of o10 6 cells/kg was as high as 35%, and that yields were especially low in older patients with ASO.…”
Section: Discussionsupporting
confidence: 91%
“…21 Although BMMNC or M-PBMNC intramuscular implantation has been used most often, both therapies have some risk: to collect about 500 mL of BMMNC, general anesthesia of about 4 h duration is necessary, and to collect PBMNC, about 3 h of apheresis with G-CSF treatment is required. [2][3][4][5][6][7][8][9][10][11][14][15][16][17][18] In a first cell-therapy trial, results of which were published in 2002, 22 ASO patients (44 limbs) were implanted with either BMMNC or PBMNC. 2 At 6 months after implantation, both therapies yielded improvements in terms of rest pain, ABI and transcutaneous oxygen pressure, but the clinical outcomes for BMMNC were significantly better than those for PBMNC.…”
Section: Introductionmentioning
confidence: 99%
“…These results remained stable until the 24-week follow-up. Two other studies, using a similar approach in seven and eight patients with CLI, confirmed the safety and feasibility of intramuscular BM-MNC transplantation in PAOD (128,129). Moreover, Higashi et al assessed an improvement in endothelium-dependent vasodilatation after BM-MNC implantation in these patients with limb ischemia.…”
Section: Peripheral Arterial Occlusive Diseasementioning
confidence: 78%
“…Although much research has been done regarding the safety and efficacy of BM-MNC transplant in treatment of lower extremity ischemic disease, 12 this research is preclinical trials, with small sample size and with no placebo control. A case study has been reported with 8 patients with thromboangiitis obliterans, in which 1 sudden death occurred after intramuscular implantation of BM-MNCs.…”
Section: Discussionmentioning
confidence: 99%